2020
DOI: 10.1111/jocs.14499
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of baseline C‐reactive protein levels on mortality after transcatheter aortic valve implantation

Abstract: Objectives: To determine whether baseline C-reactive protein (CRP) levels can predict mortality after transcatheter aortic valve implantation (TAVI), we performed a meta-analysis of currently available studies.Methods: All studies investigating the prognostic impact of baseline (preprocedural) CRP levels on all-cause mortality after TAVI were identified by means of searching PubMed and Google Scholar through May 2019. For each study, (preferentially, adjusted rather than unadjusted) odds/hazard ratios (ORs/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In addition to moderate or greater tricuspid regurgitation, higher serum C‐reactive protein was a significant risk factor of mortality in this study, although it did not reach statistical significance in the multivariate analysis. Similarly, a meta‐analysis of 14 studies including 3499 TAVR candidates demonstrated that a baseline higher C‐reactive protein level was associated with midterm all‐cause mortality 6 . Elevated C‐reactive protein might indicate advanced cardiac cachexia among other clinical conditions, thus explaining the reported poor outcomes following TAVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to moderate or greater tricuspid regurgitation, higher serum C‐reactive protein was a significant risk factor of mortality in this study, although it did not reach statistical significance in the multivariate analysis. Similarly, a meta‐analysis of 14 studies including 3499 TAVR candidates demonstrated that a baseline higher C‐reactive protein level was associated with midterm all‐cause mortality 6 . Elevated C‐reactive protein might indicate advanced cardiac cachexia among other clinical conditions, thus explaining the reported poor outcomes following TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis of 14 studies including 3499 TAVR candidates demonstrated that a baseline higher C-reactive protein level was associated with midterm all-cause mortality. 6 Elevated C-reactive protein might indicate advanced cardiac cachexia among other clinical conditions, thus explaining the reported poor outcomes following TAVR.…”
Section: Risk Factors Of Mortality Following Tavrmentioning
confidence: 99%
“…Prior studies showed that chronic inflammation might be related to increased mortality in AS patients following TAVI [5]. Condado et al showed that neutrophil-lymphocyte ratio and platelet-lymphocyte ratio could be used to risk-stratify AS patients after TAVI [16].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, transcatheter aortic valve implantation (TAVI) is an alternative treatment option to surgical aortic valve implantation in patients with inoperable and high-risk severe symptomatic AS [3]. Prior studies revealed that several biomarkers, such as galectin-3, growth differentiation factor-15, microRNAs, and brain natriuretic peptides, were known to predict outcomes after TAVI [4,5]. Moreover, in a meta-analysis of 14 studies including 3449 TAVI patients, high-baseline inflammatory status, assessed by C-reactive protein (CRP) levels, may predict increased mid-term mortality following TAVI [5].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Elevated pre-implant CRP levels are also associated with increased postoperative complications, hospital length of stay (HLOS), all-cause death, and longterm mortality in patients after various cardiovascular interventions. [9][10][11][12] Besides, in patients with HF, high CRP levels correlate with more severe symptoms and are independently associated with increased mortality and morbidity. 13 A recent study demonstrated that pre-implant CRP could predict postoperative complications and mortality in patients with LVAD support.…”
Section: Introductionmentioning
confidence: 99%